2010
DOI: 10.1039/b914460a
|View full text |Cite
|
Sign up to set email alerts
|

Microfabricated arrays for high-throughput screening of cellular response to cyclic substrate deformation

Abstract: Mechanical forces play an important role in regulating cellular function and have been shown to modulate cellular response to other factors in the cellular microenvironment. Presently, no technique exists to rapidly screen for the effects of a range of uniform mechanical forces on cellular function. In this work, we developed and characterized a novel microfabricated array capable of simultaneously applying cyclic equibiaxial substrate strains ranging in magnitude from 2 to 15% to small populations of adherent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
136
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 52 publications
3
136
0
Order By: Relevance
“…19 ␤-Catenin has also been shown to regulate myofibroblast differentiation in endothelial cells, 20 epithelial cells, 21 renal fibroblasts, 22 and lung fibroblasts. 23,24 Moreover, we 25 and others 26,27 have shown that ␤-catenin activity can be modulated by mechanical forces, suggesting that ␤-catenin may mediate mechanically regulated signal transduction. Taking this evidence together, we hypothesized that ␤-catenin mediates TGF-␤-induced VIC myofibroblast differentiation in a matrix stiffness-dependent manner.…”
Section: See Accompanying Article On Page 474mentioning
confidence: 99%
“…19 ␤-Catenin has also been shown to regulate myofibroblast differentiation in endothelial cells, 20 epithelial cells, 21 renal fibroblasts, 22 and lung fibroblasts. 23,24 Moreover, we 25 and others 26,27 have shown that ␤-catenin activity can be modulated by mechanical forces, suggesting that ␤-catenin may mediate mechanically regulated signal transduction. Taking this evidence together, we hypothesized that ␤-catenin mediates TGF-␤-induced VIC myofibroblast differentiation in a matrix stiffness-dependent manner.…”
Section: See Accompanying Article On Page 474mentioning
confidence: 99%
“…Runx2 is an essential transcription factor for osteoblast differentiation and chondrocyte maturation [54]; TAZ binds to Runx2 and to the transcription factor peroxisome proliferator-activated receptor (PPARg), the relative activation of Runx2 and PPARg determine MSC osteogenic or adipogenic tendencies and MSCs depleted of TAZ show increased adipogenesis at the expense of osteogenesis [53]. Wnt signalling and b-catenin nuclear translocation regulate MSC proliferation and differentiation [55], interact with TAZ [56] and are increasingly studied in the context of MSC mechanobiology [57][58][59]. Downregulation of nuclear b-catenin coincides with the induction of the adipogenic transcription factors [60], and b-catenin signalling therefore mediates inhibition of MSC adipogenesis resulting from applied mechanical strain [58].…”
Section: Molecules Linking Mesenchymal Stem Cell Contractility With Lmentioning
confidence: 99%
“…Commercial LOC platforms for the analysis of molecules, such as DNA or proteins, are available, and several LOC platforms have been recently developed to handle cells [57,58] and tissue constructs [59,60]. The potential advantages of increased parallelism, smaller sample sizes, and computer-controlled automation of experiments motivates our search for effective micromanipulation techniques, which can be included in LOC platforms.…”
Section: Microtechnology Platforms For Life-science Applicationsmentioning
confidence: 99%